ELECTRON MICROSCOPY OF THE HUMAN SYNOVIAL MEMBRANE - Barland, Peter (The Rockefeller University Press, 1962)
The structure of the lining cells at the surface of the synovial membrane facing the joint cavity has been studied by electron microscopy. The long cytoplasmic processes of these cells appear to be oriented toward the surface of the membrane, where they overlap and intertwine. The matrix of the lining cells contains dense material but no fibers with the periodicity of collagen. The lining cells are divided into two cell types or states of activity on the basis of their cytoplasmic contents. Type A is more numerous and contains a prominent Golgi apparatus, numerous vacuoles (0.4 to 1.5 microns in diameter) containing varying amounts of a dense granular material, many filopodia, mitochondria, intracellular fibrils, and micropinocytotic-like vesicles. Type B contains large amounts of ergastoplasm with fewer large vacuoles, micropinocytotic-like vesicles, and mitochondria. The probable functions of these cells are discussed in the light of current knowledge of the metabolism and function of the synovial membrane.